Perawatan Gigi yang dilakukan Mahasiswa Pengguna Ortodonti Cekat di Universitas Mulawarman pada Masa Pandemi Covid-19: Dental Care Performed by Students Using Fixed Orthodontics at Mulawarman University during the COVID-19 Pandemic - Ananda Putri Apriliyana; Masyhudi Masyhudi; Saiful Rokhim (Jurnal Sains dan Kesehatan, 2023)
Fixed orthodontic treatment requires the ability to maintain dental and oral hygiene which is more difficult and takes a long time, continuously, and some orthodontic procedures produce droplets and aerosols, so many orthodontic patients have to postpone their treatment schedule to minimize the risk of spreading COVID-19. The purpose of this study was to find out how dental care was carried out by students using fixed orthodontics at Mulawarman University during the COVID-19 pandemic. This research is a descriptive observational research type and the sample was selected by simple random sampling technique. The sample consisted of 96 respondents from 13 faculties at Mulawarman University. The data obtained are primary data from the questionnaire. The results showed that more respondents brushed their teeth twice a day (59.38%), consumed sugar (48.96%), visited the dentist (44.79%) and were willing to attend dentist appointments during the COVID-19 pandemic. (50%), used a soft toothbrush (38.54%), and did not use dental hygiene aids (56.25%). It is hoped that the results of this study can be useful for further research related to oral hygiene for fixed orthodontic users so that proper oral hygiene maintenance during orthodontic treatment can be carried out. Keywords: fixed orthodontics, dental care, oral hygiene, pandemic, droplet, aerosol Abstrak Perawatan ortodonti cekat membutuhkan kemampuan pemeliharaan kebersihan gigi dan mulut yang lebih sulit dan memakan waktu yang lama, berkelanjutan, serta beberapa prosedur ortodonti menghasilkan droplet dan aerosol, sehingga banyak pasien pengguna ortodonti yang harus menunda jadwal perawatan mereka untuk meminimalisir risiko penyebaran COVID-19. Tujuan penelitian ini adalah untuk mengetahui cara perawatan gigi yang dilakukan mahasiswa pengguna ortodonti cekat di Universitas Mulawarman pada masa pandemi COVID-19. Penelitian ini merupakan jenis penelitian observasional deskriptif dan sampel dipilih dengan teknik simple random sampling. Sampel terdiri dari 96 responden yang berasal dari 13 Fakultas di Universitas Mulawarman. Data yang diperoleh yakni data primer dari kuesioner. Hasil penelitian menunjukkan responden lebih banyak menyikat gigi dua kali sehari (59,38%), mengonsumsi gula (48,96%), mengunjungi dokter gigi (44,79%) dan bersedia menghadiri janji temu dengan dokter gigi selama masa pandemi COVID-19 (50%), menggunakan tipe sikat gigi soft (38,54%), dan tidak menggunakan alat bantu kebersihan gigi (56,25%). Diharapkan hasil penelitian ini dapat bermanfaat untuk penelitian selanjutnya terkait kebersihan mulut bagi pengguna ortodonti cekat sehingga pemeliharaan kebersihan mulut yang tepat selama perawatan ortodonti dapat dilakukan. Kata Kunci: ortodonti cekat, perawatan gigi, kebersihan mulut, pandemi, droplet, aerosol